The influence of adolescent pregnancy on the younger sisters of African American girls - Bernard, Yolanda (Kansas State University, 2008)
Adolescent pregnancy has been an ongoing concern in society for many years. This concern is even greater among the African American community. Girls who experience a pregnancy or childbirth during adolescence often experience difficulties in school and future careers, as well as financial and mental instability. This report will examine how the pregnancy and childbirth experiences of African American teens influence their younger female siblings.
Keywords: Adolescent pregnancy; Sibling relationships; African Americans and adolescent pregnancy; Black Studies (0325); Health Sciences, Mental Health (0347)